An analysis of well-being in urban Nigeria. Issue 2 (17th February 2018) - Rigon, Andrea
ABSTRACT: Improving the well-being of Nigerians is the aim of Nigeria Vision 20:2020, the key development policy document in Nigeria. However, as well-being is an emerging and contested concept, this article explores how the well-being of urban citizens is understood in Nigeria, and identifies key trends affecting urban well-being as expressed by a selection of strategic elite stakeholders in Nigerian society. These included senior civil servants and politicians, and various senior members of civil society groups and academia. The analysis also reveals characteristics underpinning policies for urban well-being.